The Philosophy of Aristotle - Bambrough, Renford (New York New American Library, 1963)
Offers a selection from the Greek philosopher's major works, including Metaphysics, Logic, Physics, Psychology, Ethics, Politics and Poetics; along with a contemporary reevaluation showing his continuing influence in the modern world
Keywords: Philosophy -- Aristotle -- Philosophy, Ancient